Maqashid Sharia-Based Performance dan Sharia Governance pada Bank Umum Syariah di Indonesia - Rudi Ferdiansah; Agus Hidayat; Feri Hardiyanto (Cakrawala Repositori IMWI)
This research is motivated by the importance of measuring the performance of Islamic Commercial Banks (BUS) which is not only oriented towards profitability, but also on the implementation of the principles of Maqashid al-Syariah and good sharia governance. The study aims to analyze the effect of Maqashid Sharia-Based Performance (MSI) and Sharia Governance Index (SGI) on the financial performance of BUS in Indonesia for the period 2019–2024. The study uses a quantitative approach with a panel data Fixed Effects method on 8 BUS with a total of 48 bank-year observations. The analysis was conducted using Driscoll-Kraay robust standard errors to address heteroscedasticity and autocorrelation. The results show that MSI, SGI, and the MSI×SGI interaction have a positive and significant effect on Return on Assets (ROA). In addition, ESG Score, bank size, and CAR have a positive effect, while NPF and BOPO have a negative effect on ROA. These findings indicate that the integration of Maqashid Sharia principles and strong sharia governance can improve the profitability and sustainability of BUS. This research provides practical implications for regulators and management of Islamic banks in developing a more comprehensive sharia-based performance evaluation system.